2023
DOI: 10.1021/acsanm.3c02803
|View full text |Cite
|
Sign up to set email alerts
|

Intrinsic Carbon Defects in Nitrogen and Sulfur Doped Porous Carbon Nanotubes Accelerate Oxygen Reduction and Sulfur Reduction for Electrochemical Energy Conversion and Storage

Abstract: Defects and morphology engineering is a serviceable strategy to boost the electrochemical energy conversion and storage performance of carbon-based materials. In this study, nitrogen/sulfur codoped carbon nanotubes (NS-CNTs) were first obtained via the pyrolysis of presynthesized polyaniline nanotubes with micelles composed of methyl orange and ferric chloride acting as the soft template. Furthermore, intrinsic carbon defects and mesopores were introduced to obtain etched NS-CNTs (ENS-CNTs) composites by ammon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 59 publications
0
7
0
Order By: Relevance
“…The CS/U cathode displays a rock-bottom initial specific capacity of 629.8 mAh g –1 , which drops rapidly to 263.3 mAh g –1 after 200 cycles. By adding KOH into the mixed solution of chitosan and urea, the specific capacity is increased (881.1 and 484.6 mAh g –1 for the initial and 200th cycles, respectively) for the CS/U–K cathode, which can be attributed to the abundant intrinsic carbon defects generated by KOH etching. , Compared to the stand-alone CS/U cathode, the pristine g-C 3 N 5 cathode shows superior specific capacities (752.2 and 340.4 mAh g –1 for the initial and 200th cycles, respectively), demonstrating that the N-rich moieties in g-C 3 N 5 can provide more active sites for the sulfur redox process. The limited nitrogen content in the CS/U cathode results in a finite density of active sites for the SRR process.…”
Section: Resultsmentioning
confidence: 94%
See 2 more Smart Citations
“…The CS/U cathode displays a rock-bottom initial specific capacity of 629.8 mAh g –1 , which drops rapidly to 263.3 mAh g –1 after 200 cycles. By adding KOH into the mixed solution of chitosan and urea, the specific capacity is increased (881.1 and 484.6 mAh g –1 for the initial and 200th cycles, respectively) for the CS/U–K cathode, which can be attributed to the abundant intrinsic carbon defects generated by KOH etching. , Compared to the stand-alone CS/U cathode, the pristine g-C 3 N 5 cathode shows superior specific capacities (752.2 and 340.4 mAh g –1 for the initial and 200th cycles, respectively), demonstrating that the N-rich moieties in g-C 3 N 5 can provide more active sites for the sulfur redox process. The limited nitrogen content in the CS/U cathode results in a finite density of active sites for the SRR process.…”
Section: Resultsmentioning
confidence: 94%
“…All of them exhibited one obliquely longish charging voltage plateau at 2.2–2.3 V and two discharging voltage plateaus at approximately 2.3–2.4 and 2.1 V, respectively. The charging voltage plateaus at 2.2–2.3 V were assigned to the oxidation process of solid Li 2 S 2 /Li 2 S to solid S 8 via soluble LiPS intermediates. , In contrast, the discharging plateau at a higher voltage (2.3–2.4 V) was closely related to the inverse reduction of solid S 8 first to the long-chain soluble LiPS (e.g., Li 2 S 8 , Li 2 S 6 , and Li 2 S 4 ) intermediates, while the discharging plateau at a lower voltage (2.1 V) was related to the further reduction of LiPS intermediates to the solid Li 2 S 2 /Li 2 S deposited in the hosts. It has been demonstrated that the second discharging platform is the specific capacity-determining process with a contribution of three-quarters of the total theoretical specific capacity. ,, It is believed that a higher capacity ratio of the second stage to the first stage ( Q H / Q L ) value indicates better sulfur redox performance.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…FeP/NPCNT and CV-FeP/NPCNT samples were prepared by modifying previously reported procedures. 49,50 FeCl 3 ·6H 2 O (0.5406 g) was first reacted with methyl orange (0.0658 g) in 30 mL of deionized water to form micelles as a soft template for the formation of polyaniline nanotubes. Ammonium persulfate (0.2282 g), aniline (0.274 mL), phytic acid (5.8 mL) and sulfuric acid (0.5 mol L −1 , 30 mL) were placed into the micelles solution in proper sequence under vigorous stirring.…”
Section: Methodsmentioning
confidence: 99%
“…Beyond nitrogen as a dopant, the carbon-based catalysts were developed by doping boron, phosphorus, sulfur, halides, etc. , Binary heteroatom doping on the carbon substrate further improved the ORR activity by a synergistic effect. The binary-doped carbon material consists of nitrogen as the most common heteroatom with boron, sulfur, phosphorus, and halides used as the secondary doping element. The ternary heteroatom doping of various nonmetals was reported for their superior ORR activity. Despite several combinations reported in the literature, the nitrogen and boron-codoped carbon materials exhibit the highest activity due to the electropositive boron as the active site for oxygen adsorption.…”
Section: Introductionmentioning
confidence: 99%